Using of the platform moodle in teaching russian language to foreign students - Писарь, Надежда (Didactics of the Russian language and the problems of translation for a foreign audience, 2020)
The author analyzes of the use of the electronic learning environment Moodle in teaching Russian as a foreign language to non-philological students. By the example of the author’s electronic course “Russian as a foreign language in the educational-scientific and educational-professional Sphere of Communication”, designed to train foreign students who receive a profession in the field of shipbuilding and ship operation, it is demonstrated how to form in Moodle training material taking into account personal characteristics of students, to intensify their independent activities, as well as increase the motivation of inophones to learn the language of the future specialty. Also, based on this course, methodological techniques are demonstrated that allow you to systematize and semantize highly specialized terminology, combined with the topics “Objects of marine engineering” and “Hydromechanics”, to more effectively develop the constructions of the scientific style of speech, to form reading, writing, compression, listening, comprehension and understanding skills on study, popular-science, journalistic texts and video clips; to develop communicative and discursive communication skills on educational-scientific and educationalprofessional topics.